Electrospinning of poly(l‐lactide‐co‐dl‐lactide) copolymers: Effect of chemical structures and spinning conditions. Issue 2 (10th July 2013) - Thammawong, Chakrit; Buchatip, Sutawan; Petchsuk, Atitsa; Tangboriboonrat, Pramuan; Chanunpanich, Noppavan; Opaprakasit, Mantana; Sreearunothai, Paiboon; Opaprakasit, Pakorn
<x xml:space="preserve">Abstract</x> Nanofibers of poly(L‐lactide‐co‐DL‐Lactide) (PDLLAx) copolymers with DL‐lactate (DLLA) contents of 0, 2.5, 7.5, and 50%, which exhibit strong structure/properties correlation, were fabricated by electrospinning. Effect of the copolymer structure and electrospinning conditions on morphology and properties of the fibers were examined by SEM, DSC, XRD, and tensile measurements. Bead‐free fibers of PDLLAx prepared from a DMF/CHCl3 mixed solvent are roughly 10‐times smaller in size (600–800 nm), with lower degree of surface porosity, compared to those of CHCl3. When CHCl3 is employed, an increase in size (2.4–5.5 μm) and surface porosity (0–45%) with relative humidity value is observed in crystallizable copolymers, whereas an amorphous copolymer shows a reverse trend. Thermal properties and chain arrangements of the electrospun fibers are critically affected by DLLA content of the copolymers and electrospinning conditions, as a result from interplay between intermolecular and intramolecular hydrogen bonding. Contents of crystalline domains and "physical crosslinks" generated from DL lactate segments are proposed as the origin of this phenomenon. Fiber mats of PDLLA with 50% DLLA content show a large improvement in all aspects of mechanical properties, which are suitable for various biomedical applications. POLYM. ENG. SCI., 54:472–480, 2014. © 2013 Society of Plastics Engineers